Effectiveness and color stability of non-vital dental bleaching photoactivated by violet LED on blood-stained teeth - de Almeida, Eran Nair Mesquita [UNESP]; Silva, Aryvelto Miranda; Besegato, João Felipe; de Sousa Gomes Costa, Joatan Lucas [UNESP]; Manzoli, Tatiane Miranda [UNESP]; de Andrade, Marcelo Ferrarezi [UNESP]; Kuga, Milton Carlos [UNESP] (Elsevier, 2023)
Background: Few studies have investigated the effect of violet LED irradiation associated or not with bleaching agents on blood-stained teeth. This in vitro study aimed to evaluate the whitening efficacy and color stability of non-vital dental bleaching using 35% hydrogen peroxide (HP) photoactivated with violet LED (VL) compared to 35% HP alone and 35% HP photoactivated with blue LED (BL). Methods: Fifty bovine dental crowns were used to obtain specimens of 5 × 5 × 2 mm. After selection based on a previous colorimetric analysis, the specimens were blood-stained and randomly assigned into five groups (n = 10): control (no treatment); 35% HP, 35% HP/BL; 35% HP/VL; and VL. Three bleaching sessions were performed and the colorimetric analysis (∆Eab, ∆L, and ∆WID) was recorded after 7 days, 30 days, and 9 months of the last bleaching session. Two-way repeated measures ANOVA followed by Bonferroni post-hoc test was used at a significance level of 5%. Results: 35% HP, 35% HP/BL, and 35% HP/VL showed higher values of ∆Eab, ∆L, e ∆WID (P < 0.05), without intra- and intergroup differences (P > 0.05). C and VL were similar in all the evaluation times (P > 0.05), showing lower values of ∆Eab, ∆L, and ∆WID (P < 0.05). Conclusions: 35% HP/VL can be a viable alternative for dental bleaching in endodontically-treated teeth, showing bleaching efficacy similar to 35% HP solely used, even after a 9-month follow-up. VL used alone was not effective to bleach blood-stained teeth.
Keywords: Blue LED; Color change; Dental bleaching; Hydrogen peroxide; Violet LED